Vitamin D - deficiency states: some aspects of influence to the course and outcome of pregnancy = Витамин D - дефицитное состояние: некоторые аспекты влияния на течение и исход беременности - G. S. Manasova; A. A. Zelinsky; O. N. Kazarenko; C. C. Globa (Kazimierz Wielki University, 2015)
Manasova G. S., Zelinsky A. A., Kazarenko O. N., Globa C. C. Vitamin D - deficiency states: some aspects of influence to the course and outcome of pregnancy = Витамин D - дефицитное состояние: некоторые аспекты влияния на течение и исход беременности. Journal of Education, Health and Sport. 2015;5(7):507-520. ISSN 2391-8306. DOI 10.5281/zenodo.21538 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A507-520 https://pbn.nauka.gov.pl/works/595839 http://dx.doi.org/10.5281/zenodo.21538 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015.   VITAMIN D - DEFICIENCY STATES: SOME ASPECTS OF INFLUENCE TO THE COURSE AND OUTCOME OF PREGNANCY ВИТАМИН D - ДЕФИЦИТНОЕ СОСТОЯНИЕ: НЕКОТОРЫЕ АСПЕКТЫ ВЛИЯНИЯ НА ТЕЧЕНИЕ И ИСХОД БЕРЕМЕННОСТИ   G. S. Manasova, A. A. Zelinsky, O. N. Kazarenko, C. C. Globa Г. С. Манасова, А. А. Зелинский, О. Н. Казаренко, С. С. Глоба   Odessa National medical university, Odessa, Ukraine; Communal Health Protection Institution "Maternity Hospital N 5", Odessa, Ukraine Одесский национальный медицинский университет, г. Одесса, Украина; КУ «Родильный дом № 5», г. Одесса, Украина             Summary. The article presents a review of literature on vitamin D-deficiency during pregnancy: preeclampsia, intrauterine growth retardation. Some aspects of vitamin D impact to a pregnant woman immune system, realization of intrauterine infection in the form of early neonatal sepsis; and the development of somatic pathology in children born from mothers with vitamin D-deficient status are discussed. Keywords: vitamin D- deficiency, pregnancy.   Реферат. В статье представлен обзор литературы по проблемам витамин D-дефицитного статуса во время беременности: преэклампсии беременных, задержки внутриутробного развития плода. Представлены отдельные аспекты влияния витамина D на состояние иммунной системы беременной, на реализацию внутриутробного инфицирования в виде раннего неонатального сепсиса, а также развитие соматической патологии у детей, рожденных от матерей с витаминD-дефицитным статусом. Ключевые слова: витамин D- дефицит, беременность.